Learning styles of wayuu students in public universities of the department of La Guajira, Colombia - Pitre-Redondo, Remedios; Sánchez-Martínez, Norma Margarita; Hernández-Palma, Hugo Gaspar (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article is addressed to identify the learning styles observed in students of the Wayuu ethnic group, from public universities in the department of La Guajira, Colombia. From the methodological context, the study is characterized as descriptive with a quantitative approach. The sample consisted of 210 students selected through an intentional sampling of the institutions: Universidad de la Guajira (Uniguajira), and Universidad Nacional Abierta y a Distancia (UNAD). The results show that: active, reflective and pragmatic learning styles, predominate in the students under study; and to a lesser extent, the theoretical style is present. It is concluded that learning styles are not mutually exclusive, since a combination or alternation of these can occur in order to achieve high value learning, at different times, contexts or circumstances.